A Comparison of Financial Indicators: The Case of Detroit. (4th December 2015) - Stone, Samuel B.; Singla, Akheil; Comeaux, James; Kirschner, Charlotte
Abstract : Financial condition analysis is a critical task for public managers, but it is still unclear which indicators are the most salient measures of financial well‐being. The financial health of Detroit, Michigan is unequivocally poor, providing an interesting case to evaluate the financial condition indicators that currently exist. We calculate the key financial indicators using data from Detroit over the last 11 years. We find the indicators fall into three groups: those that show no sign of impending financial crisis, those that show a steady worsening financial condition, and those that demonstrate a substantial change immediately prior to filing bankruptcy.